On the Teachability of Figurative Language: Teachers’ Perceptions of the Role of Metaphor in English Language Teaching in Chile - Veliz, Leonardo; Smith, Scott (Colombian Applied Linguistics Journal, 2021)
This paper reports on a qualitative study that examined the perceptions of English teachers towards the ‘teachability’ of metaphorical language in Chilean EFL classrooms. The study aimed at gaining a better understanding of teachers’ perceptions of the role of metaphor in the English language classroom. A group of six in-service English teachers participated in this qualitative study. Data were gathered through semi-structured interviews, which addressed three broad dimensions: (i) the views and definitions of metaphor; (ii) the teachability of metaphorically used language; and (iii) preparedness to teach metaphor. The data were thoroughly coded and analyzed thematically. The results revealed that, despite an apparently heightened awareness of the presence and role of metaphor in culture, this did not permeate the participants’ teaching practices, thus calling for more explicit preparation in teacher education programs and radical changes to the ‘educational culture’ that is still imbued with dominant neoliberal ways of doing and thinking.